Improving the Targeting of Tubulin-Binding Agents: Lessons from Drug Resistance Studies - Verrills, N.; Kavallaris, M. (Current pharmaceutical design, 2005)
Natural product drugs that target the tubulin/microtubule system remain an important component in the therapeutic arsenal to treat many types of malignancies. Agents such as the taxanes and vinca alkaloids bind to β-tubulin and disrupt microtubule dynamics by inducing a potent mitotic block and subsequent cell death. Understanding why certain cancers do not respond to treatment or develop resistance has been the subject of numerous studies in recent years. An increasing body of evidence suggests that alterations in the drug target, such as tubulin mutations, altered microtubule dynamics, altered tubulin isotype expression, and modifications in microtubule regulatory proteins, are key mechanisms of antimicrotubule drug resistance. In addition, recent work indicates that other cytoskeletal proteins that can regulate microtubule dynamics through signaling or structural interactions may be important determinants of antimicrotubule resistance. As our understanding of drug action and resistance mechanisms has increased, we can now begin to exploit these to design strategies that overcome, or counteract resistance, hence improving the efficacy of antimicrotubule agents for the treatment of cancer. This review highlights the major areas of investigation as they relate to the tubulin/microtubule system and discusses opportunities that potentially exist for improved therapeutic benefit in the treatment of drug resistant disease.